2014
DOI: 10.1002/jps.24165
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Cenderitide‐Eluting Stent I —An Antirestenosis and Proendothelization Approach

Abstract: Despite the success that drug eluting stents (DES) have achieved for minimizing in-stent restenosis (ISR), the anti-restenotic agents used in DES have been implicated in delayed endothelial healing and impairment of endothelial functions. Cenderitide (CD-NP) is a novel anti-proliferation chimeric peptide of semi-endothelial origin, thus this paper aims to demonstrate the selectivity aspect of this new peptide via in vitro evaluation on key players in ISR—smooth muscle cells (SMCs) and endothelial cells (ECs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…We postulate that its semi-endothelial nature is not likely to inhibit ECs. Our in vitro cell studies 30 showed that CD-NP did not inhibit the growth of ECs, suggesting that CD-NP displayed cell-type discrimination inhibition. Our current in vivo study showed that CES has almost 100% endothelial coverage above struts, and between struts at 28 days.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We postulate that its semi-endothelial nature is not likely to inhibit ECs. Our in vitro cell studies 30 showed that CD-NP did not inhibit the growth of ECs, suggesting that CD-NP displayed cell-type discrimination inhibition. Our current in vivo study showed that CES has almost 100% endothelial coverage above struts, and between struts at 28 days.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the PEG-co-PCL copolymer excipient also helps by making the release less sensitive to emulsification condition 29 . Base on the in vitro cell studies 30 , the last group (10% 1k PEG-10k PCL) with 10% CD-NP loading was selected for further in vivo study, as it gave measurable subsequent release following an initial burst of ~27%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,103,104] are not perfect solutions. They have a limited diversity of their structures and adverse reactions can be caused by these polymers [105]. It is necessary that the biomaterial used to cover the stent should have good mechanical properties, appropriate surface properties, excellent hemocompatibility, good biocompatibility, and drug delivery capability.…”
Section: Interests and Application Of Pdmmlasmentioning
confidence: 99%
“…Cendiritide (CD- NP) is a recombinant engineered natriuretic peptide that combines elements of naturally occurring C- and D-type NP which optimizes its agonist action on both GC-A and B 65 , and may have unique anti-fibrotic activity. Combined with bio-engineered scaffolds and other drug delivery methods this novel peptide holds particular promise for vascular as well as myocardial disease 66,67 .…”
Section: Introductionmentioning
confidence: 99%